Prevalensi Infestasi Cacing Gastrointestinal Pada Kambing (Capra sp.) Yang Dipelihara Secara Intensif Dan Semi Intensif - Aulia Khirqah; Rokhmani Rokhmani; Edy Riwidiharso (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
The main purpose of this study are to compare gastrointestinal worm species founds in goats, to compare prevalence and intensity in goats under intensive and semi intensive rearing system and to compare sex-wise and age related prevalence and intensity of gastrointestinal worms in goat. This research was conducted in intensive and semi intensive goat farms in Desa Klareyan, Kecamatan Petarukan, Pemalang using survey method with purposive random sampling technique in November 2020. Gastrointestinal worms species found in goat feces under intensive rearing system are Strongyloides sp., Haemonchus sp., Oesophagostomum sp., Trichostrongylus sp., and Ascaris sp. while species founded in goats under semi intensive rearing system are Strongyloides sp., Haemonchus sp., Oesophagostomum sp., Trichostrongylus sp., Ascaris sp., Moniezia expansa, Moniezia benedeni, Fasciola sp., And Schistosoma sp. The intensity of gastrointestinal worm eggs in goat under intensive rearing system was 1184.44±1743,28, its higher than the intensity in goats under semi intensive rearing system which has 1109.50±1573.73 (P> 0.05). The prevalence of gastrointestinal worm infestations in goats under intensive rearing system is 90%, lower than the goats under semi intensive rearing system which has 100% prevalence (Sign. 0.147). Gastrointestinal worms prevalence and intensity in male goats is lower than female goats (Sign. 0,189; P>0,05), while Gastrointestinal worms prevalence and intensity in lamb goat is higher than young goat and adult goat (Sign. 0,241; F<0,05).